2022
DOI: 10.1002/14651858.cd015395
|View full text |Cite
|
Sign up to set email alerts
|

Nirmatrelvir combined with ritonavir for preventing and treating COVID-19

Abstract: BackgroundOral nirmatrelvir/ritonavir (Paxlovid®) aims to avoid severe COVID-19 in asymptomatic people or those with mild symptoms, thereby decreasing hospitalization and death. Due to its novelty, there are currently few published study results. It remains to be evaluated for which indications and patient populations the drug is suitable. ObjectivesTo assess the e icacy and safety of nirmatrelvir/ritonavir (Paxlovid®) plus standard of care compared to standard of care with or without placebo, or any other int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 51 publications
0
17
0
1
Order By: Relevance
“…As viral burden and clinical pathology correlate, our study is also reminiscent of this phenomenon and showed that mice treated with MPV exhibited decreased clinical severity, with improvement in the clinical score, pathophysiological changes, and viral distribution compared with those in other single treatment groups. According to several studies, NTV and RDV antivirals exhibited survival rates of 36% and 21%, respectively, while MPV-treated animals had approximately 7 and 22% higher survival rates than NTV and RDV-treated animals, respectively ( Gottlieb et al, 2022 ; Jayk Bernal et al, 2022 ; Reis et al, 2022 ). In support of previous studies ( Consortium, 2021 , 2022 ; Ohl et al, 2021 ; Singh et al, 2021 ), our in vivo study also clearly illuminates the survival benefits unrelated to RDV monotherapy, which resulted in only 21% survival, although it may be of clinical significance because it has yielded improved weight loss recovery and clinical scores.…”
Section: Discussionmentioning
confidence: 99%
“…As viral burden and clinical pathology correlate, our study is also reminiscent of this phenomenon and showed that mice treated with MPV exhibited decreased clinical severity, with improvement in the clinical score, pathophysiological changes, and viral distribution compared with those in other single treatment groups. According to several studies, NTV and RDV antivirals exhibited survival rates of 36% and 21%, respectively, while MPV-treated animals had approximately 7 and 22% higher survival rates than NTV and RDV-treated animals, respectively ( Gottlieb et al, 2022 ; Jayk Bernal et al, 2022 ; Reis et al, 2022 ). In support of previous studies ( Consortium, 2021 , 2022 ; Ohl et al, 2021 ; Singh et al, 2021 ), our in vivo study also clearly illuminates the survival benefits unrelated to RDV monotherapy, which resulted in only 21% survival, although it may be of clinical significance because it has yielded improved weight loss recovery and clinical scores.…”
Section: Discussionmentioning
confidence: 99%
“…As viral burden and clinical pathology correlate, our study is also reminiscent of this phenomenon and showed that mice treated with MPV exhibited decreased clinical severity, with improvement in the clinical score, pathophysiological changes, and viral distribution compared with those in other treatment groups. According to several studies, NTV and RDV antivirals exhibited survival rates of 36% and 21%, respectively, while MPV-treated animals had approximately 7 and 22% higher survival rates than NTV and RDV-treated animals, respectively animals (6,26,34). Recent clinical studies suggest that RDV does not play a significant role in mortality, but it still plays a major role in reducing the duration and severity of illness, an important outcome when hospitals are overcrowded with patients with COVID-19 (35)(36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of 3CLpro inhibitors has become apparent with the development of nirmatrelvir (PF-07321332), a peptidomimetic reversible covalent inhibitor that is co-formulated with the pharmacokinetic enhancer ritonavir (the resulting combination being marketed as Paxlovid) [5]. When treatment is initiated during the first days after symptom onset, it results in substantial clinical benefit [6][7][8][9]. We recently demonstrated that nirmatrelvir is equipotent in vitro against the current SARS-CoV-2 variants of concern (VoC).…”
Section: Introductionmentioning
confidence: 99%